KONSEP ILMU DALAM SHAHIH AL-BUKHARI - Luqman Abdul Jabbar (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Pontianak, 2016)
Bukhari selected the authenticity of hadith so thoroughly and carefully that he was nicknamed